2019
DOI: 10.3233/wor-182849
|View full text |Cite
|
Sign up to set email alerts
|

The effects of introducing electric adjustable height desks in an office setting on workplace physical activity levels: A randomised control field trial

Abstract: BACKGROUND: Electric adjustable height desks (EAHD) have been promoted as an opportunity for desk based workers to stand at work but there is limited evidence that they have an effect on light physical activity. OBJECTIVE: The main objective was to determine if there would be a change in light physical activity with the introduction of EAHD. The secondary objective was to assess if there was an associated change in leisure time activity. METHODS: Activity levels were measured by step counts, self-reported acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 73 publications
(139 reference statements)
0
13
0
Order By: Relevance
“…Since the health risks associated with too much sedentary time add to the risks related to insufficient PA, specific strategies are required to decrease the engagement in activities such as passive screen-time ( 155 ). Strategies applied to break long sitting periods include the use of electric adjustable-height desks that alternate between sitting and standing positions ( 156 ), as well as treadmill desks ( 157 ) and bike desks ( 158 ). However, the aforementioned options are not accessible for many, are not environmentally sustainable, and are not practical and/or appealing enough for several people ( 62 , 159 , 160 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the health risks associated with too much sedentary time add to the risks related to insufficient PA, specific strategies are required to decrease the engagement in activities such as passive screen-time ( 155 ). Strategies applied to break long sitting periods include the use of electric adjustable-height desks that alternate between sitting and standing positions ( 156 ), as well as treadmill desks ( 157 ) and bike desks ( 158 ). However, the aforementioned options are not accessible for many, are not environmentally sustainable, and are not practical and/or appealing enough for several people ( 62 , 159 , 160 ).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of sedentary behavior outcomes, seven studies used only a self-report outcome measure, for example, questionnaire (Coffeng et al, 2014;Graves et al, 2015;Puig-Ribera et al, 2015;Blake et al, 2019;Lithopoulos et al, 2020;Rollo and Prapavessis, 2020;Patel et al, 2021), four used a device-based measure, for example, an ActivPAL (Neuhaus et al, 2014;Tobin et al, 2016;Carter et al, 2020;Weatherson et al, 2020), and 11 used a combination of self-report and device-based measure (Chau et al, 2014;Dutta et al, 2014;De Cocker et al, 2016;Healy et al, 2016;Danquah et al, 2017;Li et al, 2017;Dunning et al, 2018;Edwardson et al, 2018;Maylor et al, 2018;Mantzari et al, 2019;Pierce et al, 2019).…”
Section: Sedentary Behavior Outcomesmentioning
confidence: 99%
“…Six studies showed changes in number of breaks (Coffeng et al, 2014;De Cocker et al, 2016;Mantzari et al, 2019;Carter et al, 2020;Rollo and Prapavessis, 2020;Patel et al, 2021). All studies showed changes in sitting time (Chau et al, 2014;Coffeng et al, 2014;Dutta et al, 2014;Neuhaus et al, 2014;Graves et al, 2015;Puig-Ribera et al, 2015;De Cocker et al, 2016;Healy et al, 2016;Tobin et al, 2016;Danquah et al, 2017;Li et al, 2017;Dunning et al, 2018;Edwardson et al, 2018;Maylor et al, 2018;Blake et al, 2019;Mantzari et al, 2019;Pierce et al, 2019;Carter et al, 2020;Lithopoulos et al, 2020;Rollo and Prapavessis, 2020;Weatherson et al, 2020;Patel et al, 2021). Seventeen studies showed changes for increased standing (Chau et al, 2014;Dutta et al, 2014;Neuhaus et al, 2014;Graves et al, 2015;De Cocker et al, 2016;Healy et al, 2016;Tobin et al, 2016;Danquah et al, 2017;Li et al, 2017;Edwardson et al, 2018;Maylor et al, 2018;Mantzari et al, 2019;Pierce et al, 2019;…”
Section: Sedentary Behavior Outcomesmentioning
confidence: 99%
“…Three studies used only subjective self-report measures (Engelen et al, 2016;Renaud et al, 2018;Wallmann-Sperlich et al, 2019), and 13 studies used only objective measures (Candido et al, 2019;Carr et al, 2016;Gilson et al, 2012;Gorman et al, 2013;Koepp et al, 2013;Lindberg et al, 2018;Mansoubi et al, 2016;Maylor et al, 2018;Miyachi et al, 2015;Schuna et al, 2014;Tobin et al, 2016;Wahlstrom et al, 2019;Zhu et al, 2018). Both subjective and objective physical activity measures were used simultaneously in 10 studies (Bergman et al, 2018;Chau et al, 2014Chau et al, , 2016Dutta et al, 2014Dutta et al, , 2019Eyler et al, 2018;Jancey et al, 2016;Malaeb et al, 2019;McGann et al, 2015;Pierce et al, 2019). Subjective physical activity was measured using the Occupational Sitting and Physical Activity Questionnaire (OSPAQ) in five studies and the International Physical Activity Questionnaire (IPAQ) in two studies.…”
Section: Physical Activity and Sedentary Behavior Measurementsmentioning
confidence: 99%
“…Among the eight randomized control trials, findings were reported on overall physical activity in two studies (Bergman et al, 2018;Miyachi et al, 2015), physical activity at work in two studies (Chau et al, 2014;Tobin et al, 2016), and both overall and at work physical activity in four studies (Dutta et al, 2014;Maylor et al, 2018;Pierce et al, 2019;Schuna et al, 2014). Four sit-stand desk intervention studies found that providing sit-stand desks had a little effect on workers' overall or work-related physical activity when compared with traditional-sitting desks (Chau et al, 2014;Dutta et al, 2014;Pierce et al, 2018;Tobin et al, 2016).…”
Section: Randomized Control Intervention Study Findingsmentioning
confidence: 99%